Pemetaan Platform Media Komunikasi Pemasaran PT. Dyandra Promosindo dalam Ruang Publik di Surabaya - Putra, Bayu Pratama; Prasetyo, Iwan Joko (Jurnal Komunikasi Profesional, 2017)
This study aims to determine the mapping of marketing communication media platform conducted by PT. Dyandra Promosindo Surabaya in the exhibition of Indie Clothing Expo 8th. This study discusses mapping of marketing communication media platform through promotion mix seen from the use of advertising element, personal selling, and direct marketing. The analysis of this research using qualitative approach with descriptive method, data collecting technique is with documentation, in-depth interview, observation, and data search field. Informant research as many as three people, involving branch manager PT. Dyandra Promosindo, and Project Manager and Promotion Officer of Indie Clothing Expo 8th Exhibition. Data analysis techniques include data reduction, display data, and Conclusion Drawing and evaluation. The result of this research is in mapping of usage of advertising element, PT. Dyandra Promosindo utilizes various advertising media as a means to promote Indie Clothing Expo exhibition 8th from promotion cooperation with some print media such as newspaper and magazine, then some local radio, and informative account in social media, and use of outdoor promotional media starting from billboards, billboards , Until the cutting sticker in public transportation. In addition, PT. Dyandra Promosindo maximizes personal sales through the ICE Agent program by working with fifty representatives of high school students in Surabaya. And finally, the use of ticketbox as a direct marketing strategy by adding a promo program to improve the service and the number of visitors, as well as maintaining the brand image of the exhibition. Keywords: Platform Mapping, Promotional Mix, Descriptive Quantitative